2019
DOI: 10.1159/000502795
|View full text |Cite
|
Sign up to set email alerts
|

Low-Stage Gastric MALT Lymphoma Causing Life-Threatening Upper Gastrointestinal Bleeding

Abstract: Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is an uncommon tumor of the stomach that only comprises around 1-6% of all tumors of the stomach. Non-Hodgkin lymphoma more commonly affects the lymph nodes and may spread to the spleen and bone marrow, whereas extranodal non-Hodgkin lymphoma is less common. Primary gastric lymphoma is further divided based on histologic features; one of the types is MALT lymphoma, which is strongly associated with Helicobacter pylori infection. The first sign of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…Song et al 7 also reported GI bleeding in 19 (15.6%) patients but did not comment on the hemodynamic instability, which appears to be sparsely reported. Obleagă et al 8 and Bestari et al 9 reported a case each of upper GI hemorrhage with hypovolemic shock as the first sign of MALT lymphoma which was similar to our case.…”
Section: Discussionsupporting
confidence: 88%
“…Song et al 7 also reported GI bleeding in 19 (15.6%) patients but did not comment on the hemodynamic instability, which appears to be sparsely reported. Obleagă et al 8 and Bestari et al 9 reported a case each of upper GI hemorrhage with hypovolemic shock as the first sign of MALT lymphoma which was similar to our case.…”
Section: Discussionsupporting
confidence: 88%
“…Only 15.6% of cases have been reported with upper GI bleeding [7]. Life-threatening acute bleeds are rare and seldom described in a few case reports [5,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Eliminating infection diminishes the risk of developing atrophic gastritis and gastric cancer. Although the low incidence of gastric cancer in Indonesia is due to low H. pylori infection, early diagnosis and treatment of symptomatic patients is necessary to decrease the risk of chronic complications [ 51 , 73 , 75 ].…”
Section: Methodsmentioning
confidence: 99%